The Essentiality of Educational Financing Planning in Improving Service Quality (Case Study at SDN Ciluncat 1) - H. Soro , Suharyanto; Nissa, Dina Hairun; Fauzia, Dhita Annisa Fauzia3. (Global Education Journal, 2025)
Effective financing planning is a problem in the efficient management of educational units, which has a direct impact on the quality of service. This study aims to find and analyze educational financing planning in improving the quality of services at SDN Ciluncat 1. The researcher used a case study approach with a collection method using observation, interviews, and documentation. The results of the study indicate that educational financing planning is carried out objectively, factually, and based on school needs can improve the quality of service. This finding concludes that the importance of systematic financing planning in creating sustainable educational service quality.